2013
DOI: 10.1016/j.cell.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations of the Immunoglobulin Framework Are Generally Required for Broad and Potent HIV-1 Neutralization

Abstract: Summary Broadly neutralizing antibodies to HIV-1 (bNAbs) can prevent infection and are therefore of great importance for HIV-1 vaccine design. Notably, bNAbs are highly somatically mutated and generated by a fraction of HIV-1-infected individuals several years after infection. Antibodies typically accumulate mutations in the complementarity determining region (CDR) loops, which usually contact the antigen. The CDR loops are scaffolded by canonical framework regions (FWRs) that are both resistant to and less to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
527
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(562 citation statements)
references
References 77 publications
32
527
0
3
Order By: Relevance
“…Influenza neutralizing Abs have substantial SHM. Particularly high levels of SHM, 15-30% amino acid mutation (2,3), are present and necessary for broad Ab neutralization of diverse HIV strains (4,5). Therefore, as candidate influenza and HIV vaccines are evaluated for the ability to induce broadly neutralizing antibodies (bnAbs), the quantitation and functional characterization of GC responses will be a key parameter for study.…”
mentioning
confidence: 99%
“…Influenza neutralizing Abs have substantial SHM. Particularly high levels of SHM, 15-30% amino acid mutation (2,3), are present and necessary for broad Ab neutralization of diverse HIV strains (4,5). Therefore, as candidate influenza and HIV vaccines are evaluated for the ability to induce broadly neutralizing antibodies (bnAbs), the quantitation and functional characterization of GC responses will be a key parameter for study.…”
mentioning
confidence: 99%
“…For example, framework mutations can compensate for the destabilizing effect of mutations at CDRs needed for antigen binding (15). In other cases, non-CDR SHMs have been shown to be required for the neutralization activity of broadly neutralizing anti-HIV antibodies (16).…”
mentioning
confidence: 99%
“…Thus far, the roles of SHM have been studied primarily by examining the functional consequences of reverting the somatic mutation of selected antibodies back to the germline sequences (15)(16)(17)(18)(19)(20)(21). Although these studies have demonstrated that antibodies depend on somatic mutations to achieve high-affinity antigen binding, the approach is limited to the small set of mutations present in a given antibody.…”
mentioning
confidence: 99%
“…Tfhs are essential to help germinal center B cells undergo somatic hypermutation and affinity selection (34,35). It is noteworthy that the frequencies of total circulating "Tfh-like" cells correlate with the production of broadly neutralizing antibodies (34), which are typically highly mutated (36).…”
mentioning
confidence: 99%